PENGARUH PROPORSI KEPEMILIKAN INSTITUSIONAL, UKURAN DEWAN KOMISARIS INSTITUSIONAL TERHADAP RETURN ON ASSETS DENGAN ACCRUAL EARNINGS MANAGEMENT SEBAGAI VARIABEL INTERVENING - Heni Yusnita, M.Ak. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
This study aims to determine the effect of good corporate governance which is proxied by the proportion of institutional ownership and the size of the board of commissioners on return on assets with accrual earnings management as an intervening variable manufacturing company in the property and real estate sectors listed on the Indonesia Stock Exchange in 2017-2019. By using a path analysis the results of the study found that the proportion of institutional ownership influences accrual earnings management, the size of institutional board of commissioners influences accrual earnings management, the proportion of institutional ownership and the size of the board of commissioners together affect the accrual earnings management. The proportion of institutional ownership has no effect on return on assets, the size of the institutional board of commissioners has an effect on return on assets, accrual earnings management has an effect on return on assets, the proportion of institutional ownership, the size of the board of commissioners and accrual earnings management together influence return on assets. Accrual earnings management can act as an intervening variable on the effect of the proportion of institutional ownership on return on assets. Accrual earnings management can act as an intervening variable on the effect of institutional board size on return on assets.